A novel magnetic fluorescent molecularly imprinted sensor for highly selective and sensitive detection of 4-nitrophenol in food samples through a dual‐recognition mechanism. (30th June 2021) - Zhu, Wenting; Zhou, Yushun; Liu, Shuai; Luo, Mei; Du, Jun; Fan, Jieping; Xiong, Hua; Peng, Hailong
Highlights: CDs uniformly distributed into MIPs layers of MF-MIPs sensor. The imprinted sites of MF-MIPs sensor exhibited a dual recognition capability. MF-MIPs sensor showed excellent selectivity, sensitivity, rapidity, and reuse. MF-MIPs sensor can detect trace 4-NP with accuracy, reliability and practicality. Abstract: In this study, surface imprinting, magnetic separation, and fluorescent detection were integrated to develop a dual-recognition sensor (MF-MIPs), which was used for highly selective and sensitive detection of 4-nitrophenol (4-NP) in food samples. Silane-functionalized carbon dots (Si-CDs) participated in the imprinting process and were uniformly distributed into the MIPs layers. MF-MIPs sensor exhibited a high fluorescence response and selectivity based on the dual-recognition mechanism of imprinting recognition and fluorescence identification. The relative fluorescence intensity of MF-MIPs sensor presented a good linear relationship in the range of 0.08–10 μmol·L −1 with a low limit of detection (23.45 nmol·L 1 ) for 4NP. MF-MIPs sensor showed high anti-interference, as well as excellent stability and reusability. The 4-NP recovery from spiked food samples ranged from 93.20 to 102.15%, and the relative standard deviation was lower than 5.0%. Therefore, MF-MIPs sensor may be a promising method for 4-NP detection in food samples.